Kesenian Eco-print Hapazome pada Tekstil sebagai Antitesis Environmentally Unfriendly Textile Dyestuff - Sri Utami; Igb Bayu Baruna Ariesta; Nyoman Ayu Permata Dewi (Abdi Seni, 2022)
Today’s fashion business is concerned about the environmentally unfriendly or ecologically unfavorable problem of textile industry waste. It is well recognized that dyes have hazardous effects on living organisms, and industrial textile waste in general can be in the form of effluents (liquid waste) including dye residual substances.  Because it contaminates the water, textile dye waste is particularly unfavorable to the environment. Based on this, researchers design a textile using the Hapazome dyeing technique, which is an eco-friendly method of dying. This method falls under the category of eco-printing or natural printing. Hapazome technical art is one of the Japanese art which means leaf-dye. By hitting the leaf’s top surface against a piece of fabric, researchers apply Hapazome technique which can create a copy of the leaf’s motif form on fabric.  The motifs designed by researchers in the creation of textiles were chosen from one of Balinese cultures, that is, Balinese script. The choice of Balinese script as the primary theme for creating textile designs attempts to demonstrate one of Balinese local identities. Thus, the nuances and characteristics of the local Balinese are built into the fabrics that researchers created. Using the approach of art creation, research is done on the art of eco-printing Hapazome on textiles as the antithesis of environmentally unfriendly textile dyestuff. The method of art creation is a way of systematically putting a work of art into real.